Mindfulness‐based practices with family carers of adults with learning disability and behaviour that challenges in the UK: Participatory health research - Tina Cook; Steven Noone; Megan Thomson (Wiley, 2019)
Abstract Background Family carers of adults with learning disability and behaviours that challenge lead complex and stressful lives. Their caring role can leave them isolated and unsupported. In the UK, effective services designed to build resilience for people in long‐term caring roles are lacking. There are none (to our knowledge) designed using a participatory health research (PHR) approach with family carers and professionals. Objective With positive behaviour support (PBS) and mindfulness and acceptance and commitment therapy (ACT) as key elements, a PHR approach was used to understand the basis for a successful course that supported the capabilities and resilience of family members in long‐term caring roles. Design The research was guided by the principles of PHR with participation as the defining principle throughout. Central to the research were reflexive conversations (communicative spaces) where diverse knowledges were shared and critiqued. Findings Mindfulness/ACT can change long‐standing response behaviours and build personal resilience and improve mental health. Elements enabling positive change included a facilitation approach for collaborative reflexivity and the complementary, interactive approach to collaborative enquiry for learning and decision making afforded by PHR. Discussion The use of PHR accessed knowledges that would have been lost to more traditional, professional‐expert driven processes and facilitated change in constructs for action for both professionals and family carers. Findings challenge service providers to consider how experiential knowledge has agency in professional practice and service design. Reflection on the PHR process across the FaBPos project led to a re‐consideration of quality issues in relation to PHR and participation.